2004
DOI: 10.1590/s0001-37652004000200036
|View full text |Cite
|
Sign up to set email alerts
|

Species richness and relative abundance of birds in natural and anthropogenic fragments of Brazilian Atlantic forest

Abstract: Bird communities were studied in two types of fragmented habitat of Atlantic forest in the State of Paraná, southern Brazil; one consisted of forest fragments that were created as a result of human activities (forest remnants), the other consisted of a set of naturally occurring forest fragments (forest patches). Using quantitative data obtained by the point counts method in 3 forest patches and 3 forest remnants during one year, species richness and relative abundance were compared in those habitats, consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 4 publications
4
20
1
4
Order By: Relevance
“…Similar findings have been presented in various case studies examining these two different habitat types in countries around the world (e.g. Anjos 2004;Augenfeld, Franklin, and Snyder 2008;Martin and Blackburn 2010). From a silvicultural perspective, the SF plots are over-matured with homogenous walnut tree stands; natural regeneration was rarely seen due to the high level of human impact, which means that the future development of these habitats is not yet secure.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Similar findings have been presented in various case studies examining these two different habitat types in countries around the world (e.g. Anjos 2004;Augenfeld, Franklin, and Snyder 2008;Martin and Blackburn 2010). From a silvicultural perspective, the SF plots are over-matured with homogenous walnut tree stands; natural regeneration was rarely seen due to the high level of human impact, which means that the future development of these habitats is not yet secure.…”
supporting
confidence: 77%
“…Research studies investigating bird habitats (Sekercioglu 2002;Simon, Schwab, and Otto 2002;Anjos 2004;Naidoo 2004;Uezu, Metzger, and Vielliard 2005;Round, Gala, and Brockelman 2006) have shown that bird species richness and abundance are strongly dependent on the vertical and horizontal heterogeneity of habitats, and that these two parameters can be good indicators with which to assess structural changes occurring within forests. In terms of the results presented here, although no strongly significant relationship between vegetation variables and bird diversity was observed, a considerable dependence can be seen between selected indicator bird species and certain forest flora parameters.…”
Section: Relationship Between Bird Diversity and Forest Vegetationmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study, also carried out in the state of Paraná, showed that naturally fragmented landscapes do not necessarily have higher connectivity (Anjos, 2004). This study shows that, in comparison to a humanfragmented landscape, the bird community in a naturally fragmented landscape is not strongly influenced by connectivity.…”
Section: Discussionsupporting
confidence: 39%
“…PEMG comprises approximately 650 ha and is considered the best conserved SAF remnant in the region. The area has high biological integrity (Silveira 2006;Anjos 2004) and was designated a high priority site for biodiversity conservation by a Brazilian Ministry of Environment panel of specialists (MMA 2002).…”
Section: Study Areamentioning
confidence: 99%